Health providers pass knowledge and abilities acquired by training in obstetric emergencies to their peers: the average treatment on the treated effect of PRONTO on delivery attendance in Mexico - Jimena Fritz; Héctor Lamadrid-Figueroa; Gustavo Angeles; Alejandra Montoya; Dilys Walker (BMC Pregnancy and Childbirth, 2018)
Abstract Background A significant proportion of newborn and maternal deaths can be prevented through simple and cost-effective strategies. The main aim of this study was to evaluate the impact of the PRONTO obstetric-emergency management training for improving evidence-based birth attendance practices among providers attending the training at 12 hospitals in three states of Mexico from 2010 to 2012, and to estimate dissemination of the training within the hospitals. Methods The average treatment on the treated effect of the PRONTO intervention for the probability of performing certain practices during birth attendance was estimated in a sample of 310 health providers. Impact estimates were obtained by performing provider-level matching using a mixed Mahalanobis distance one-to-one nearest-neighbor and exact matching approach. A secondary analysis estimated the positive externalities caused by the intervention in the treated hospitals using the same analytical approach. Provider-level fixed effects regression models were used to estimate the rate of decay of the probability of performing the examined practices. Results Providers attending the PRONTO training showed significant increases in the probability of performing the complete active management of the third stage of labor, especially the first and third steps, and skin-to-skin-contact. There was a negative and significant effect on the probability of performing uterine sweeping. Providers who did not attend the training in treated hospitals also showed marked significant changes in the same practices, except for uterine sweeping. There was no evidence of a significant decay of the probability of performing the routine practices over time among the treated providers. Conclusions PRONTO is efficacious in changing trained providers’ behavior, but not on all practices, suggesting that some practices are deeply ingrained. The results also suggest that information on practices is effectively transmitted to peers within treated hospitals. Previous findings of the dilution of the effect of PRONTO on some practices seem to be more related to the rotation of personnel (mainly interns) rather than providers returning to their former habits. Trial registration NCT01477554. Registered on November 18, 2011; retrospectively registered.